Sokongan sosial bagi penghidap HIV positif di Malaysia - Najwa Afiqa Roshaizad,; Aizan Sofia Amin,; Haikal Anuar Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The HIV positive cases in Malaysia and the world are increasing from day to day among individuals of all races and ages. However, the issue of social support for HIV positive patients still needs to be discussed in detail as this issue will have an impact on the lives of HIV positive patients in Malaysia. The focus of this study is to examine social support among HIV positive people in Malaysia. This study used a full qualitative method to collect and analyze data. Five male informants with HIV positive were involved in this study. All informants were interviewed separately using semi structured interview methods. Among the topics discussed in this study were family acceptance, the type of social support they received and the social support resources. The findings showed that, four out of five informants were infected with the HIV viruses from sharing needle and one informant was infected from unprotected sex. The results showed that they received adequate social support in terms of emotions, information, instrumental and networking from various sources. Nevertheless, social support for HIV positive people in Malaysia still needs to be discussed and promoted to ensure their psychological well-being.